The cultural and economic value of sports events in rural areas: Media and legal context - Đorđević Vladimir; Jeličić Goran (Ekonomski Signali, 2025)
The cultural and economic value of sports events in rural areas represents a multidimensional phenomenon encompassing local development, the preservation of cultural identity, and the strengthening of social cohesion. Research shows that sports manifestations in smaller communities contribute to economic activity through increased tourism spending, support for small and medium-sized enterprises, and the generation of seasonal employment. At the same time, they serve as a means of promoting cultural heritage and the local way of life, thus fostering a sense of belonging and community. The media context plays a crucial role in the visibility and sustainability of these events. Coverage in local and regional media enables better positioning of rural municipalities on the cultural and tourist map of the country and increases the potential to attract sponsors and investors. On the other hand, the legal framework governing the organization of sports events in rural areas must align with the principles of transparency, safety, and responsibility in order to ensure long-term benefits for the local community. Given all the above, an intersectoral approach is needed-one that integrates sports policy, cultural development, media strategy, and legal regulation. Only through such coordination can the full potential of sports events as a tool for integrated rural development be realized.